Co-treatments to Boost IDO Activity and Inhibit Production of Downstream Catabolites Induce Durable Suppression of Experimental Autoimmune Encephalomyelitis - Lemos, Henrique; Mohamed, Eslam; Ou, Rong; McCardle, Caroline; Zheng, Xiaozhong; McGuire, Kris; Homer, Natalie Z. M.; Mole, Damian J.; Huang, Lei; Mellor, Andrew L. (Frontiers in Immunology, 2020)
Reinforcing defective tolerogenic processes slows progression of autoimmune (AI) diseases and has potential to promote drug-free disease remission. Previously, we reported that DNA nanoparticles (DNPs) and cyclic dinucleotides (CDNs) slow progression of experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis, by activating the Stimulator of Interferon Genes (STING) signaling adaptor to stimulate interferon type 1 (IFN-I) production, which induced dendritic cells to express indoleamine 2,3 dioxygenase (IDO) and acquire immune regulatory phenotypes. Here, we show that therapeutic responses to DNPs depend on DNA sensing via cyclic GAMP synthase (cGAS) and interactions between Programmed Death-1 (PD-1) and PD-1 ligands. To investigate how increased tryptophan (Trp) metabolism by IDO promotes therapeutic responses mice were co-treated at EAE onset with DNPs and drugs that inhibit kynurenine aminotransferase-II (KatII) or 3-hydroxyanthranilic acid dioxygenase (HAAO) activity downstream of IDO in the kynurenine (Kyn) pathway. DNP and KatII or HAAO inhibitor co-treatments suppressed EAE progression more effectively than DNPs, while KatII inhibition had no significant therapeutic benefit and HAAO inhibition attenuated but did not prevent EAE progression. Moreover, therapeutic responses to co-treatments were durable as EAE progression did not resume after co-treatment. Thus, using STING agonists to boost IDO activity and manipulating the Kyn pathway downstream of IDO is an effective strategy to enhance tolerogenic responses that overcome autoimmunity to suppress EAE progression.